miR-203 Inhibits Alcohol-Induced Hepatic Steatosis by Targeting Lipin1 - Cheng, Xiao-Yu; Liu, Jun-Da; Lu, Xin-Yi; Yan, Xing; Huang, Cheng; Meng, Xiao-Ming; Li, Jun (Frontiers in Pharmacology, 2018)
Alcohol abuse is a leading cause of liver disease characterized by liver inflammation, fatty liver, alcoholic hepatitis, or liver cirrhosis. Alcoholic fatty liver (AFL) disease is associated with the excessive accumulation of lipids in hepatocytes as well as oxidative stress. MicroRNA-203 (miR-203) is known to suppress the proliferation and metastasis of hepatocellular carcinoma, but the role in the progression of alcoholic liver disease is not unclear and is warranted for investigation. In the present study, we have found the expression of miR-203 is down-regulated in Gao-Binge alcoholic mice model and ethanol induced AML-12 cell lines in vitro. Furthermore, over-expression miR-203 decrease the lipids accumulation in liver and ethanol induced AML-12 cell. Mechanistically, we identified that Lipin1 is a key regulator of hepatic lipid metabolism, and is acted as a downstream target for miR-203. In conclusion, our results suggested that miR-203 over-expression inhibited the liver lipids accumulation and the progression of alcoholic fatty liver by targeting Lipin1.